Remote Monitoring and Control for an Isolate Prototype Substation Model - Sandhya Rani G; Vijaya Laxmi U; Srividya Devi P; Naga Sandhya Rani M (E3S Web of Conferences, 2021)
The objective of this paper is to monitor the electrical parameters like voltage, current, etc., remotely and display all the obtained real time values for a substation isolate. This paper is furnished to assure the load and electrical system equipment by the activation of relay, whenever the acquired parameters exceed the predefined values. Generally, this Proposed system design makes use of microcontroller, but the prototype of this circuit modelled in Proteus and can be executed by using ATmega 168 microcontroller. When supply is given to the designed hardware, all the sensors start sensing their respective parameters i. e., voltage, current, temperature etc., and modernize all the values on the display. Comparison between the problem-solving time values and the preordained values is continuously carried out by the microcontroller, if any of these values go beyond the pre-defined values, it sends fault alert to the relay, updates it on the screen and sends the same as an SMS through GSM for the rectification.